From Eye Care to Hair Growth: Bimatoprost - Marco Zeppieri; Caterina Gagliano; Leopoldo Spadea; Carlo Salati; Ekele Caleb Chukwuyem; Ehimare Samuel Enaholo; Fabiana D'Esposito; Mutali Musa (MDPI AG, 2024)
Background: Bimatoprost has emerged as a significant medication in the field of medicine over the past several decades, with diverse applications in ophthalmology, dermatology, and beyond. Originally developed as an ocular hypotensive agent, it has proven highly effective in treating glaucoma and ocular hypertension. Its ability to reduce intraocular pressure has established it as a first-line treatment option, improving management and preventing vision loss. In dermatology, bimatoprost has shown promising results in the promotion of hair growth, particularly in the treatment of alopecia and hypotrichosis. Its mechanism of action, stimulating the hair cycle and prolonging the growth phase, has led to the development of bimatoprost-containing solutions for enhancing eyelash growth. Aim: The aim of our review is to provide a brief description, overview, and studies in the current literature regarding the versatile clinical use of bimatoprost in recent years. This can help clinicians determine the most suitable individualized therapy to meet the needs of each patient. Methods: Our methods involve a comprehensive review of the latest advancements reported in the literature in bimatoprost formulations, which range from traditional eye drops to sustained-release implants. These innovations offer extended drug delivery, enhance patient compliance, and minimize side effects. Results: The vast literature published on PubMed has confirmed the clinical usefulness of bimatoprost in lowering intraocular pressure and in managing patients with glaucoma. Numerous studies have shown promising results in dermatology and esthetics in promoting hair growth, particularly in treating alopecia and hypotrichosis. Its mechanism of action involves stimulating the hair cycle and prolonging the growth phase, leading to the development of solutions that enhance eyelash growth. The global use of bimatoprost has expanded significantly, with applications growing beyond its initial indications. Ongoing research is exploring its potential in glaucoma surgery, neuroprotection, and cosmetic procedures. Conclusions: Bimatoprost has shown immense potential for addressing a wide range of therapeutic needs through various formulations and advancements. Promising future perspectives include the exploration of novel delivery systems such as contact lenses and microneedles to further enhance drug efficacy and patient comfort. Ongoing research and future perspectives continue to shape its role in medicine, promising further advancements and improved patient outcomes.